Caesarean delivery before 39 weeks associated with selecting an auspicious time for birth in Taiwan. Issue 3 (September 2015) - Chu, Kuei-Hui; Lee, Yu-Hsiang; Tai, Chen-Jei; Lin, Yu-Hung; Huang, Chiu-Mieh; Chien, Li-Yin
Abstract Background Caesarean delivery before 39 weeks of gestation increases the risk of morbidity among infants. Taiwan has one of the highest caesarean rates in the world, but little attention has been paid to this issue. This study aimed to describe the rate of caesarean delivery before 39 weeks gestation among women who did not have labour signs and had a non-emergency caesarean delivery in Taiwan and to examine whether the phenomenon was associated with the Chinese cultural practice of selecting an auspicious time for birth. Methods We recruited women at 15–28 weeks of pregnancy at 5 hospitals in northern Taiwan and followed them at 4 or 5 weeks after delivery using structured questionnaires. This analysis included 150 primiparous mothers with a singleton pregnancy who had a non-emergency caesarean delivery without the presence of labour signs. Results Ninety-three of these women (62.0%) had caesarean deliveries before 39 weeks of gestation. Logistic regression analysis showed that women who had selected an auspicious time for delivery (OR = 2.82, 95% CI: 1.15–6.95) and delivered in medical centres (OR = 5.26, 95% CI: 2.25–12.26) were more likely to deliver before 39 weeks of gestation. Conclusion Non-emergency caesarean delivery before 39 weeks of gestation was common among the study women, and was related to the Chinese cultural practice of selecting an auspicious time for birth. Further studies are needed to examine the risks and benefits associated with timing of caesarean delivery in Taiwan in order to generate a consensus among obstetricians and give pregnant women appropriate information.